2021
DOI: 10.2166/wst.2021.230
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic digestion of dried/shredded food waste in a periodic anaerobic baffled reactor

Abstract: The objective of the current work is to study the impact of the operational parameters' variation (HRT, OLR and T) on biomethane productivity in a Periodic Anaerobic Baffled Reactor (PABR). The feedstock used was a biomass product named FORBI (Food Residue Biomass), which is dried and shredded source-separated household food waste. The Periodic Anaerobic Baffled Reactor (PABR) is an innovative, high-rate bioreactor. Apart from the Hydraulic Retention Time (HRT) and the Organic Loading Rate (OLR), an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In addition to the switching frequency, there are two switching manners viable for the PABR viewing from the top, namely, "clockwise sequential" (Figure 1C) and "every second" (Figure 1D). Most studies found in the literature focus on the "clockwise sequential" switching manner for synthetic (Skiadas and Lyberatos, 1998;Skiadas et al, 2000;Stamatelatou et al, 2003Stamatelatou et al, , 2004, real industrial (Liu et al, 2009;Stamatelatou et al, 2009), or municipal (Zarkaliou et al, 2022) wastewater and food residue biomass (Mathioudakis et al, 2021) treatments, although simulation taken from the study by Skiadas and Lyberatos (1998) predicted that the "every second" option seemed to lead to slightly higher performance and less fluctuation of the effluent concentration compared with the "clockwise sequential".…”
mentioning
confidence: 99%
“…In addition to the switching frequency, there are two switching manners viable for the PABR viewing from the top, namely, "clockwise sequential" (Figure 1C) and "every second" (Figure 1D). Most studies found in the literature focus on the "clockwise sequential" switching manner for synthetic (Skiadas and Lyberatos, 1998;Skiadas et al, 2000;Stamatelatou et al, 2003Stamatelatou et al, , 2004, real industrial (Liu et al, 2009;Stamatelatou et al, 2009), or municipal (Zarkaliou et al, 2022) wastewater and food residue biomass (Mathioudakis et al, 2021) treatments, although simulation taken from the study by Skiadas and Lyberatos (1998) predicted that the "every second" option seemed to lead to slightly higher performance and less fluctuation of the effluent concentration compared with the "clockwise sequential".…”
mentioning
confidence: 99%